The investigation of chest circumference on lung capacity in netball, football and hockey among female athletes / Maisarah Ibrahim - Ibrahim, Maisarah (Faculty of Sport Science and Recreation, 2016)
Pulmonary test is the test that can be enabling to measure the ability how efficient the lungs work. Spirometry was important as the maneuver or equipment as application for accessing the respiratory diseases providing the recommendation, indications and contraindication when use the device [4]. Thus, this study conducted to determine how much air entering into the lung based on three categories of sports which are netball, football and hockey female athletes and also to identify does chest circumferences were related towards the sports itself. 52 female athletes were recruited in the study. They were asked to fill up the demographic form and informed consent also chest circumference measurement before started the spirometer test which the test had measure FVC, FEV1, FEV1/FVC, and PEF reading variables. One-way ANOVA was used to investigate to make comparison of the sports with pulmonary function test's variables while correlation was used in order to measure relationship between CM with those variables. The result shows there was significance different between categories of sports with the FVC reading, and there was no significance different between categories of sport with FEV1, FEV1/FVC and PEF reading. The prediction for those sports showed that athletes who were exercises, tend to have higher value in FVC reading because of large muscle worked throughout regular training. There was no significance relationship between CM and PFT's reading variable. As for conclusion, the results of this present study conclude that the type of sports determines each of the pulmonary function variables and chest circumference does not influenced lung capacity at all.